2003
DOI: 10.1159/000070878
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Pediatric Cerebral Arteriovenous Malformations after Angiographically Documented Resection

Abstract: Angiographically confirmed surgical resection is believed to be the ‘gold standard’ for cure in the treatment of intracranial arteriovenous malformations (AVMs). However, rare exceptions of recurrent AVMs have been documented. We are aware of 11 reported cases of recurrent AVMs in which complete resection of the initial lesion was confirmed by postoperative angiography. Eight of these cases were in the pediatric population. In this report, we present 2 additional cases of such recurrent lesions, review the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 23 publications
4
49
0
2
Order By: Relevance
“…2,8,19 Only 18%-20% of patients with AVMs present before 15 years of age, 13,17 with hemorrhage and seizure being the most common primary events. 1,5,31,32 Treatment of AVMs includes microsurgical resection, radiosurgery, endovascular embolization, or a combination of these strategies. 3,6,24,28 Accumulating evidence has demonstrated that AVMs recur in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,8,19 Only 18%-20% of patients with AVMs present before 15 years of age, 13,17 with hemorrhage and seizure being the most common primary events. 1,5,31,32 Treatment of AVMs includes microsurgical resection, radiosurgery, endovascular embolization, or a combination of these strategies. 3,6,24,28 Accumulating evidence has demonstrated that AVMs recur in children.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The annual risk of hemorrhage in pediatric AVM is approximately 3.2% per year, 17 with 5%-10% risk of death and up to 50% risk of neurological morbidity. 1,12,15,17 Early and complete treatment of these malformations in children is therefore important. Current treatment options include microsurgery, endovascular embolization, radiosurgery, or combined therapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Complete excision or obliteration of the lesion usually eliminates the risks of hemorrhage, and a negative cerebral angiogram is generally considered indicative of a cure. Although recurrence of cerebral AVMs is rare, there are several reports of cerebral AVM recurrence in both children 1,2,4,[9][10][11] and adults 3,5,8,16) after complete resection verified by postoperative angiography.…”
Section: Introductionmentioning
confidence: 99%